Reconfigurable Computing: Architectures, Tools, and Applications 10th International Symposium, ARC 2014, Vilamoura, Portugal, April 14-16, 2014. Proceedings - Goehringer, Diana; Santambrogio, Marco Domenico; Cardoso, João M.P; Bertels, Koen (Theoretical Computer Science and General Issues, 2014)
This book constitutes the thoroughly refereed conference proceedings of the 10th International Symposium on Reconfigurable Computing: Architectures, Tools and Applications, ARC 2014, held in Vilamoura, Portugal, in April 2014. The 16 revised full papers presented together with 17 short papers and 6 special session papers were carefully reviewed and selected from 57 submissions. The topics covered are applications; methods, frameworks and OS for debug, over-clocking, and relocation; memory architectures; methodologies and tools; and architectures.